New insights of bacterial communities in fermented vegetables from shotgun metagenomics and identification of antibiotic resistance genes and probiotic bacteria. (July 2022) - Yasir, Muhammad; Al-Zahrani, Ibrahim A.; Bibi, Fehmida; Abd El Ghany, Moataz; Azhar, Esam I.
Graphical abstract: Highlights: Metagenomics provided comprehensive illustration of bacterial communities in pickle. Candidate novel metagenome-assembled genomes (MAGs) retrieved. Enterobacteriaceae contigs were detected in the pickle metagenomes. Pickled vegetable resistome produce resistance against clinically important antibiotics. Carbohydrate, bacteriocin, and vitamin pathways were detected in pickle metagenomes. Abstract: Consumption of fermented foods has grown worldwide due to the purported health benefits. It is thus critical to understand fermented foods microbiome that mainly influences the quality and safety of these foods. This study identified bacterial communities, including functional profiles of probiotics and antimicrobial resistance genes (ARGs), in pickled vegetables commonly consumed in the Middle Eastern, African, and Asian sub-continent regions. Eighteen samples from six pickled vegetables were collected from local markets in Saudi Arabia and analyzed using shotgun metagenomic sequencing. Statistical analyses revealed significant distance and separate clustering of bacterial communities among the different pickle types. Species of Levilactobacillus namurensis, Lentilactobacillus buchneri, Lentilactobacillus parafarraginis, Lactiplantibacillus pentosus, Pectobacterium carotovorum, Leuconostoc carnosum, Weissella confuse were found in a range of dominance in most of the samples. Binning revealed 33 high-quality, metagenome-assembled genomes (MAGs), including 4 MAGs representing putatively novel species of Lactobacillus, Alcanivorax, and Dichelobacter . Moreover, 285 ARGs and variants produce resistance against 20 classes of antibiotics were retrieved, mostly from Enterobacteriaceae contigs. The metagenomes harbored relatively high abundances of carbohydrate fermentation enzymes, as well as metabolic pathways for amino acid metabolism, cofactors and vitamins biosynthesis. Overall, by providing a comprehensive overview of bacterial communities and probiotic bacteria in pickled vegetables, the results suggest the need for more hygienic processing to avoid Enterobacteriaceae contamination and ARG spread.